Antiferromagnetic Alkali Metal Oxohydroxoferrates(III) with Correlated Hydrogen Bonding Systems. Issue 12 (26th November 2019) - Albrecht, Ralf; Hunger, Jens; Hölzel, Markus; Block, Theresa; Pöttgen, Rainer; Doert, Thomas; Ruck, Michael
Abstract: The oxohydroxoferrates(III) A 2 [Fe2 O3 (OH)2 ] ( A =K, Rb, Cs) were synthesized under hydroflux conditions. Approximately equimolar mixtures of the alkali metal hydroxides and water were reacted with Fe(NO3 )3 ⋅ 9H2 O at about 200 °C. The product formation depends on the hydroxide concentration, therefore also other reaction products, such as KFeO2, K2−x [Fe4 O7−x (OH)x ] or α ‐Fe2 O3, are obtained. The crystal structures of the oxohydroxoferrates(III) A 2 [Fe2 O3 (OH)2 ] follow the same structural principle, yet differ in their layer stacking or/and their hydrogen bonding systems depending on A and temperature. In the resulting four different orthorhombic structure types, [FeO3 OH] 4− tetrahedra share their oxide corners to create folded ∞ 2 [ Fe2 O3 (OH)2 ] 2− layers. The terminal hydroxide ligands form hydrogen bonds between and/or within the layers. The positions of the hydrogen atoms in these networks are correlated. The A + cations are located between the folded anionic layers as well as in their trenches. Under reaction conditions, the potassium compound crystallizes in the space group Cmce (Pearson symbol oC 88), showing a bimodal disorder of the hydrogen atoms in hydrogen bridges. In a virtually hysteresis‐less first‐order transition at 340(2) K, the structure slightly distorts into the room‐temperature modification with the subgroup Pbca ( oP 88), and the hydrogen atoms order. The rubidium and caesium compounds are isostructural to each other but not to the potassium compound, and are always obtained as mixtures of two modifications with space groups Cmce ( oC 88′) and Immb ( oI 88). Upon heating, the oxohydroxoferrates decompose into their anhydrides A FeO2 and water. The type of hydrogen bonding network influences the decomposition temperature, the structure and the morphology of the crystals. Despite the presence of iron(III), which was confirmed by 57 Fe‐Mössbauer spectroscopy, K2 [Fe2 O3 (OH)2 ] is diamagnetic in the investigated temperature range between 1.8 and 300 K. Neutron diffraction revealed strong antiferromagnetic coupling of the magnetic moments, which are inverted in neighboring tetrahedra. Abstract : Hydroflux conditions provide access to oxohydroxoferrates A 2 [Fe2 O3 (OH)2 ] with A =K, Rb, Cs. Hydrogen bonds inside and between layers of corner‐sharing [FeO3 OH] tetrahedra strongly influence decomposition temperatures, crystal structures and morphologies. The magnetic moments of the iron(III) cations are aligned antiparallel in neighboring tetrahedra.